Metabolic dysfunction-associated steatotic liver disease predicts graft failure in kidney transplant recipients - Kyungho Lee; Yebin Park; Hojin Jeon; Junseok Jeon; Jung Eun Lee; Wooseong Huh; Kyung-Do Han; Hye Ryoun Jang (Clinical Kidney Journal, 2026)
Abstract Introduction Metabolic dysfunction–associated steatotic liver disease (MASLD) has been established to classify steatotic liver disease more accurately. We investigated the association between MASLD score and long-term kidney transplant outcomes. Methods Kidney transplant recipients who underwent national health screening programs from 2009 to 2017 and with follow-up until 2021 were identified using the Korean National Health Insurance Service data. MASLD was defined based on cardiometabolic criteria and the fatty liver index. Results Among 8 326 kidney transplant recipients, 2 027 (24.3%) had MASLD, 25 (0.3%) had MASLD with increased alcohol intake, and 419 (5.0%) had MASLD with other liver diseases. The incidence rates of graft failure (17.5 vs. 11.3, P < 0.001) and mortality (12.5 vs. 8.9 per 1 000 person-years, P < 0.001) were significantly higher in the MASLD group than in those without steatotic liver disease. After adjusting for demographics, lifestyle, comorbidities, estimated glomerular filtration rate, and proteinuria, the adjusted hazard ratios for graft failure and mortality were 1.23 (95% confidence interval, 1.03–1.46) and 1.03 (95% confidence interval, 0.85–1.25), respectively. Conclusions This study identified MASLD as a significant risk factor for graft failure in kidney transplant recipients, highlighting the need for MASLD screening and management in kidney transplant recipients.